Competitive Strategies and Their Importance in Effective Business Management - Castro Monge, Edgar (2010)
Competitive strategies that companies develop are a key factor to determine how they will compete in the markets and if their business management will be successful. It is vital for companies to identify the most effective strategy or set of strategies to compete efficiently. Only by establishing the appropriate strategy can companies achieve their proposed goals and objectives. In order for a strategy to be successful, it must be coherent with its values and goals, resources and capabilities, environment, structure and organizational systems. This paper aims then to make an analysis of the five types of major competitive strategies discussed in literature: Miles and Snow (1978), Porter (1980), Miller (1987), Mintzberg (1988) and Kotler (1992). It tries to find similarities and differences and provide a guide for companies to establish the strategy that best fits their characteristics.